Seal Bomb Noise as a Potential Threat to Monterey Bay Harbor Porpoise - Simonis, Anne E.; Forney, Karin A.; Rankin, Shannon; Ryan, John; Zhang, Yanwu; DeVogelaere, Andrew; Joseph, John; Margolina, Tetyana; Krumpel, Anna; Baumann-Pickering, Simone (Frontiers in Marine Science, 2020)
Anthropogenic noise is a known threat to marine mammals. Decades of research have shown that harbor porpoises are particularly sensitive to anthropogenic noise, and geographic displacement is a common impact from noise exposure. Small, localized populations may be particularly vulnerable to impacts associated with displacement, as animals that are excluded from their primary habitat may have reduced foraging success and survival, or be exposed to increased threats of predation or bycatch. Seal bombs are underwater explosives used in purse seine fisheries to deter marine mammals during fishery operations. Pinnipeds are believed to be the primary target for seal bomb use, however there may be indirect impacts on harbor porpoises. Active purse seine fishing using seal bombs in the greater Monterey Bay area may, at times, span the entire range of the Monterey Bay harbor porpoise stock, which may lead to negative impacts for this population. In this contribution, we review anthropogenic noise as a threat to harbor porpoise, with a focus on the potential for impacts from seal bomb noise exposure in the Monterey Bay region.